Vascular assessment of the right internal jugular vein in low birth weight newborns - Montes Tapia, Fernando Félix; Rodríguez Taméz, Antonio; Hernández Garduño, Adolfo; Barreto Arroyo, Itzel; Rodríguez Balderrama, Isaías; O Cavazos, Manuel Enrique de la; Quero, José (informaHealthcare, 2013)
Objective: To determine the dimensions and depth of the right internal jugular vein (RIJV) in low birth weight newborns by ultrasound and assess the differences in weight and determine the relationship of the vein with the carotid artery. Method: We performed a vascular assessment of the RIJV in 100 low birth weight newborns. The subjects were divided into three groups, low birth weight (LBW) newborns, 52500 g; very low birth weight (VLBW) newborns, 51500 g; and extremely low birth weight (ELBW) newborns 51000 g. Results: Of the newborns, 39% had LBW, 33% had VLBW, and 28% had ELBW. The medians were gestational age 31 weeks, weight 1300 g, anteroposterior diameter of the RIJV 2.2 mm, and the distance from the skin–RIJV 3.6 mm. In LBW newborns, the median anteroposterior diameter of RIJV was 2.7 mm; in LBW newborns 2.2; in ELBW newborns 1.9 (p50.001); the median distance from skin to RIJV for LBW newborns was 4.1mm; for VLBW newborns, 3.6 and for ELBW newborns 2.9 (p50.01); differences that were statistically significant. Conclusions: In low birth weight newborns, the diameter and depth of the RIJV is directly proportional to the weight of the subjects studied.